Role of adenosine deaminase and lymphocyte/neutrophil ratio in the diagnosis of tuberculous pleural effusion in patients with exudative pleural effusion - Behera, Bijaya K.; TN, Sathish K. (International Journal of Research in Medical Sciences, 2017)
Background: Present study was conducted with an objective to evaluate the role of ADA and lymphocyte/neutrophil ratio in the diagnosis of tuberculous pleural effusion in patients with exudative pleural effusion and to analyze the cause of non-tuberculous exudative pleural effusion. Methods: This hospital based observational study was conducted from August 2011 to September 2013 with a total number of 120 patients of exudative pleural effusion who were admitted in medical wards of MKCG Medical College Hospital, Berhampur, Odisha, India. Patients with transudative pleural effusion, age less than 12years and those who were haemodynamically unstable were excluded from the study. Statistical analysis was done using standard statistical techniques. Results: A total number of 120 patients with exudative pleural effusion were analyzed. 83 patients were males and 37 patients were females. Maximum no of patients were seen in the age group of 21-40 years. Total ADA was found to be >40 U/L in all cases of TB effusion. All cases of TB effusion were lymphocyte predominant with L/N ratio > 0.75. In case of exudative pleural effusion due to non-tuberculous etiology L/N ratio was <0.75. P Value <0.0001 was considered extremely significant for L/N ratio for TB effusion. Conclusions: ADA value more than 100 U/L was observed only in patients of tuberculous effusion. L/N ratio was >0.75 in 97 patients of tuberculous effusion and none of the non-tuberculous effusion. Combined use of ADA and L/N ratio is more efficient means for diagnosing tuberculous pleural effusion than the use of ADA alone.